2007
DOI: 10.1080/07315724.2007.10719597
|View full text |Cite
|
Sign up to set email alerts
|

Food Components and Dietary Patterns of Two Different Groups of Mexican Lactating Women

Abstract: The energy and nutrient intakes of women were different by regional hospital and not by age. Education about the importance of the maternal diet during lactation should be directed toward increasing consumption of foods rich in micronutrients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
32
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 16 publications
5
32
2
Order By: Relevance
“…(10,14) Other studies have identified similar values. (9,12,13) In this study and in others, the dietary intake was below the recommended for women of reproductive age that perform light physical activity, which is 2,200 kcal / day plus an extra 330 kcal / day for lactation. Legend: *For a consumption higher than the recommended by the Adapted Food Pyramid in the groups of 'sugar and sweets' and 'oils and fats', a zero score was given; ** All lactating mothers consumed more than eight different items/day listed on the FFQ, but these were not quantified…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…(10,14) Other studies have identified similar values. (9,12,13) In this study and in others, the dietary intake was below the recommended for women of reproductive age that perform light physical activity, which is 2,200 kcal / day plus an extra 330 kcal / day for lactation. Legend: *For a consumption higher than the recommended by the Adapted Food Pyramid in the groups of 'sugar and sweets' and 'oils and fats', a zero score was given; ** All lactating mothers consumed more than eight different items/day listed on the FFQ, but these were not quantified…”
Section: Discussioncontrasting
confidence: 50%
“…(9,10) Other authors have shown that lactating women were within the normal range or obese. (11)(12)(13)(14) However, the interpretation of the average body mass index obtained in the postpartum phase should be done with caution as there is no specific classification for nursing mothers. Thus, the values recommended for adult women are used as a parameter, which places the lactating mothers of the study in overweight situation.…”
Section: Discussionmentioning
confidence: 99%
“…of fruits and vegetables (28,(46)(47)(48)(49) . Nevertheless, our findings do not allow comparisons between the reported patterns and different income ranges, due to the homogeneity of our sample regarding income.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of 60 lactating women sampled from across Mexico, 77% of the women had dietary folate intake below the recommended amount (Caire-Juvera et al 2007). In one study of 60 lactating women sampled from across Mexico, 77% of the women had dietary folate intake below the recommended amount (Caire-Juvera et al 2007).…”
mentioning
confidence: 99%